ARTIFICIAL INTELLIGENCE SEBAGAI ASISTEN DIGITAL DALAM PENYUSUNAN TUGAS MAHASISWA - Fadiya Malona Nasution; Mutiara Evelin Yoseva Marpaung; Rakfatul Huurul Aini; Siti Rahma Maibang; Vebilla MayNingsih; Hendra Kurnia Pulungan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of Artificial Intelligence (AI) has significantly influenced the field of education, particularly in assisting students with academic assignments. This study aims to describe the role of AI as a digital assistant in completing student assignments and to identify the benefits and challenges of its use in academic activities. The method used in this study is a literature review by examining various scientific sources related to the use of AI in education. The results show that AI can help students search for information, organize writing ideas, improve grammar, and increase the efficiency of completing assignments. However, excessive use of AI may lead to dependency, reduced critical thinking skills, and academic ethical issues such as plagiarism. Therefore, the wise use of AI and proper supervision from higher education institutions are necessary so that this technology can function as a learning support tool without reducing the quality of the learning process. With proper utilization, AI can become a digital assistant that supports the improvement of students’ academic quality in the digital era.